Variability of Agronomic Traits of Wheat (Triticum aestivum L.) Lines in Two Agroecosystems in Indonesia - Herdhani, Mira; Wahyu, Yudiwanti; Trikoesoemaningtyas (Department of Agronomy and Horticulture, IPB University, 2024)
Wheat is an important agricultural commodity in Indonesia, yet the country remains heavily reliant on imports to meet domestic demand. The diverse agroclimatic conditions in the highlands and lowlands pose significant challenges for national wheat production. This study aimed to evaluate the performance of wheat lines in two distinct altitude environments: Cipanas (1120 m above sea level) and Cisarua (600 m above sea level). An augmented randomized complete block design (RCBD) assessed 50 F6 wheat lines derived from the HP1744/”Selayar” cross. The results revealed significant variability in agronomic traits attributable to altitude differences. However, genotype-by-environment (GxE) interactions were found to be non-significant for all evaluated characters. Broad-sense heritability was classified as medium for the grain-filling period in Cipanas and seed weight of the main panicle in Cisarua, while all other traits exhibited low heritability. Based on the stress sensitivity index (SSI), 14 lines (28%) were identified as tolerant to higher temperatures in the medium-altitude environment, particularly in terms of seed weight of the main panicle. These findings are of utmost importance as they underscore the need to consider genetic and environmental factors in developing wheat cultivars suitable for Indonesia’s diverse agro-climatic conditions.